Synthesis of novel indane-1,3-dione derivatives and their biological evaluation as anticoagulant agents - Mitka, Katarzyna (Array, 2009)
Summary: 2-Substituted derivatives of indane-1,3-dione 3a–f , 5a–g, 6a–g were synthesized and investigated as anticoagulant agents. 2-Arylindane-1,3-diones (3) were obtained in the reaction of phthalide with appropriate arylaldehydes. 2-Arylmethyleneindane-1,3-diones (5) were prepared by condensation of indane-1,3-dione with the corresponding arylaldehydes. The compounds 5 were converted into their methyl analogues 6 by reduction with sodium tetrahydroborate. All of the compounds studied were screened for the anticoagulant activity. The highest prothrombin time was established for 2-[4-(methyl-sulfanyl)phenyl]indane-1,3-dione (3c) (PT = 33.71(±26.01) s), which was very close to PT of the drug anisindione (PT = 36.0(±26.42) s)